PENGOLAHAN AIR GAMBUT MENJADI AIR BERSIH SECARA KONTINYU DI DESA PEUNAGA CUT UJONG - Kiswanto Kiswanto; Wintah Wintah; Nur laila Rahayu; Endah Sulistiyowati (JURNAL LITBANG KOTA PEKALONGAN, 2019)
Peat water has a brown color, humic acid content, organic substances, iron and pH levels are very high. To overcome the problem of peat water to be made clean water need to be processing first. Continuous processing of peat water includes; Neutralization, aeration, coagulation – flokulation, and filtration is a complete set of processes but is packaged in a simple form. This process is designed according to the condition and level of education of rural communities in peat water treatment. This study was conducted at a shelter in the village of Peunaga Cut Ujong Meurebo West Aceh. This research aims to reduce acidity, color, turbidity, flavor, iron (Fe), Zeng (Zn), organic matter, nitrate (NO3), and Nitrit (NO2). The research method is an experimental that is directly applied in the field. From the laboratory results in the UPTD Health Banda Aceh has been conducted test water quality before and after processing there are significant results. The results of experimental studies through the simple design of continuous processing using natural materials such as gravel, sand, charcoal and palm fiber and the chemical filling of the capor and alum obtained the results of color dissipation achieved 93.3%, pH of 98.3%, turbidity/cloudiness reached 91.9%, organic substance (KMNO4) of 73.3%, hardness of 39.7%, iron (Fe) 94.6%, zinc (Zn) of 91.09%, Flurode 77.33%, Nitrate (NO 3) of 80.04%, and Nitrit (NO 2) 99.31%. Meanwhile, the result of peat water is no smell and feel. The results of this trial are still under the standard quality of Permenkes RI No. 416/Menkes/PER/IX/1990 on the water quality requirements. Keywords: Peat, Continuous, Coagulan, Neutralization